Powdery Mildews in the Libyan Jamahiriya. - KHAN, M. WAJID (The Libyan Journal of Agriculture, 2023)
Some powdery mildew species new to Libyan Jamahiriya are reported. This paper, sequel to the first in the series based on studies made to enlist and identify powdery mildew species infecting cultivated and wild plants in Jamahiriya, includes: Erysiphe urticae: Erysiphe communis: Sphaerotheca euphorbiae: Erysiphe pisi: Erysiphe trifolii: Erysiphe graminis: and Erysiphe convolvuli. Some of these have been observed in perithecial stage also. E. urticae: E. communis: S. euphorbiae: E. convolvuli: and E. trifolii are new to the powdery mildew’ flora of Jamahiriya. The records of E. urticae on Urticia urens: E. communis on Sisymbrium irio: S. euphorbiae on Euphorbia terracina: E. graminis on Phalaris minor: E. pisi on Vicia monant ha and Lens esculent us: E. cichoracearum on Hedypnois cretica, Conyza honor iensis and Sonchus oleraceous: E. trifolii on Melilotus indicus and Trigonella foenicum-graecum: and E. convolvuli on Convolvulus arvensis, are new to Libyan Jamahiriya. E. pisi on Vicia monantha, and E. cichoracearum on Conyza bonariensis are also new world recordings. The causal organism of powdery mildew of Papilionaceous plants known as Erysiphe polygoni in Jamahiriya is suggested to be recognised as E. pisi or E. trifolii. as the case may be, in accordance with the current taxonomic status.